Cura seca, cura úmida, cura térmica: avaliação da eficiência na resistência à compressão do concreto - Marques, Melissa Borges de Oliveira (Universidade Federal Rural do Semi-Árido, 2018)
Concrete can be used in civil construction for structural purposes, sealing, foundation, among others. Over time, new technologies have emerged and added to the requirements of the standard of quality of structures, motivated the development of new researches with the objective of developing innovative methods, procedures and materials that configure improvements in the durability and mechanical properties of concrete. Among some of the care that needs to be employed to ensure the strength and durability of the concrete is the cure, known as the set of measures that is to avoid the premature evaporation of the water necessary for the hydration of the cement. This study analyzes the axial compressive strength of concrete when cured in air, by submersion in water and thermally. For companies that work with precast, because they need large areas of storage, considerable amount of shapes, equipment and agility in the production process, humid curing at twenty-eight days becomes undesirable production. In view of this, and thanks to the innovations of the researches, the thermal cure arises, whose main purpose is to accelerate the curing process of the concrete, reaching a desired minimum resistance in a short period. A simpler, cheaper and less laborious alternative would be curing in the air or curing dry. However, the major drawback is loss of compressive strength. The concrete of this research used the trace (1: 2: 3) with water-cement ratio (a / c = 0.65). The concrete tests were carried out: in the fresh state - reduction of the cone trunk and specific mass - in the hardened state - compressive strength, ultrasonic pulse propagation velocity, absorption and porosity. The specific mass value was 2,401,25 kg / m³ and a reduction of 14 cm. The compressive strength at 28 days of concrete with dry, wet and thermal curing were: 14.54 MPa, 16.79 MPa and 16.81 MPa, respectively.
Monografia
Keywords: Concreto; Durabilidade; Qualidade; Processo produtivo; Concrete; Durability; Quality; Productive process; ENGENHARIAS::ENGENHARIA CIVIL